Вплив іт технологій на методи управління неприбутковими організаціями - Дорохін, Р. О. (ХНУРЕ, 2023)
This work is devoted to a strategic management of Nonprofit organizations using method called BMC. Types and strategic goals of Nonprofit organizations were considered. Longitudinal study that was conducted using “Month activity” forms estimated that when I implemented BMC method – understanding of organizational strategic goals and plans were better. It increased volunteers satisfaction on 180% during 3 months after method implementation. Employees of that organization are working remotely using IT services and tools, which were utilized to inform and visualize strategic goals, plans and rivals